Current clinical trends in the management of gram positive infections in Indian critical care settings: a survey - Rampal, Ritika; Ahdal, Jaishid; Kaushik, Kriti; Jain, Rishi (International Journal of Research in Medical Sciences, 2019)
Background: In India, gram-positive infections (GPIs) particularly, methicillin-resistant Staphylococcus aureus (MRSA) prevalence is reported to increase exponentially. The overall mortality rate among patients with multi drug resistant GPIs in ICU setting are as high as 16%, despite the availability of various therapeutic options. Aim of the study is to determine the burden of GPIs in critical care settings and to understand the practising behaviour among the specialists in the management of MRSA infections. Methods: The survey was conducted among 264 critical care specialists who attended the Annual National Conference of Indian Society of Critical Medicine held in February 2019 at Mumbai. The delegates were administered a validated 10 question survey. Results: In the survey, 72% of the respondents agreed to the rising prevalence of MRSA and associated increased mortality rate of >16%. Empirical gram positive cover is being given to 30-40% of ICU patients, with ABSSSI being listed as a major indication followed by CAP, VAP, CLABSI and DFI. 46% of the doctors listed vancomycin as their preferred anti-MRSA agents followed by teicolplanin and linezolid. However, more than 80% of the doctors feel that nephrotoxicity in vancomycin, thrombocytopenia in linezolid and poor biofilm penetration are major limitations of these anti-MRSA agents. Conclusions: The survey highlighted the increasing trend in the prevalence and associated mortality in GPIs in critical care settings in India. Further, the limitations of existing anti-MRSA agents have invoked the need for a newer agent with a broad spectrum anti-bacterial activity along with improved safety profile and effective biofilm penetration, which can be used as a suitable alternative empiric therapy to manage GPIs.